AB1344 Presence of echocardiographic criteria for hfpef multiplies the risk for death and cardiovascular events in patients with rheumatic diseases. (12th June 2018) - Kleinert, S.; Morbach, C.; Tony, H.-P.; Angermann, C.E.; Stoerk, S.; Breunig, M.
Abstract : Background: Patients with rheumatic diseases (RD) have an increased risk for cardiovascular (CV) disease and heart failure (HF). Clinical assessment of HF signs and symptoms in RD is often limited by functional impairment. Objectives: We investigated the prognostic value of echocardiographic and neurohormonal criteria for HF with preserved ejection fraction (HFpEF) in patients with RD. Methods: This prospective, single-centre study included consecutive RD outpatients considered at increased risk for CV events according to ESC score (≥3%), pathological ECG, or elevated NTproBNP (>200 pg/mL) as published by this group*. Clinical assessment and transthoracic echocardiography according to ESC criteria was performed. Presence of HFpEF was assumed if patients had NTproBNP >125 pg/mL, and either left ventricular hypertrophy (LVH; averaged septal-posterior wall thickness >11 mm) or left atrial dilation (LAD; LA Diameter>43 mm), regardless of presence of dyspnea. Kaplan-Meier plots were generated, and hazard ratios (HR) with 95% confidence intervals were computed using Cox regression with adjustment for age. Results: Out of 764 patients (mean age 51 years, 70% female) 46% had rheumatoid arthritis (RA), 34% systemic autoimmune diseases (SAI; connective tissue disease or vasculitis), and 20% spondylo-arthritis (SpA); 248 of these patients (mean age 61±13 years, 62% female, RA 46%; SAI 32%; SpA 22%) had valid echocardiographic data (4 patients with LV ejection fraction <50% were excluded; follow-up data was missing in 3 cases). After a median follow-up time of 5.4 years, 20.6% of patients (group 1–4: n=19/5/8/1 respectively) had died or suffered a CV event (myocardial infarction 4.1%; stroke 1.8%; decompensated HF 1.8%; resuscitation 0.9%). In univariable analysis NTproBNP >125 pg/ml (HR 3.6; 1.9–6.8, p=0.0001), LAD or LVH (HR 2.3; 1.1–4.5, p=0.02), and age per 5 years (HR 1.4, 1.2–1.6, p<0.0001) were significant predictors for an increased risk for death or CV event. Compared to the referent group consisting of patients with no signs of LVH or LAD in the presence of normal NTproBNP (group 4; n=59, 23.8%), patients with echocardiographic criteria for HFpEF (group 1; n=84, 33.9%) had a 7-fold increased risk for death or CV event: HR 7.2 (1.6–31.9; figure). The event risk for both patients with elevated NTproBNP but absent LVH or LAD (group 2; n=49, 19.8%) as patients with normal NTproBNP but presence of LVH or LAD (group 3; n=56, 22.6%) was also 5- to 6-fold increased: HR 5.5 (1.2–25.8) and 5.5 (0.9–18.2), respectively. Conclusions: In patients with RD with an increased baseline CV risk, echocardiographic criteria suggestive of HFpEF are highly relevant indicators of worse outcome (7-fold increased risk for death or CVE), in particular in conjunction with an elevated NTproBNP value, irrespective of clinical presentation. Reference: [1] Breunig, M., S. Kleinert, et al. (2017). "Simple screening tools predict death and cardiovascular events in patients with rheumatic disease."Scand J Rheumatol:1–8. Acknowledgements: This study was supported by the Competence Network Heart Failure Germany (BMBF grant 01 GI0205/01GI1202A) and the Comprehensive Heart Failure Centre Würzburg (BMBF grant 01EO1004). Disclosure of Interest: None declared